Որսորդությունը որպես ազնվական գործունեության տեսակ և հիպերմոտիվ՝«Սասնա ծռեր» էպոսում և հայ միջնադարյան մատենագրության մեջ - Համբարձումյան, Հայկ (Մատենադարան)
In the Armenian epic Sasna Tsṛer and in medieval historiography, the hypermotive of hunting is formed of various motives. In particular, the variants of the epic and the works of medieval authors such as P‘awstos Buzand, Movsēs Khorenats‘i, Movsēs Kagankatvats‘i, and Step‘anos Orbelean contain the motives of creating hunting places, liberating or finding a mountain or forest for hunting, discovering in the same place a church hidden from the heroes, murder during hunting, etc. A comparison of similar motives in the oral and literary traditions not only makes it possible to track the connections and mutual influences of the traditions but also shows the important functional and plot-forming importance of the hunting motives. From the thematic and ideological point of view, the motives of creating or finding a hunting place symbolize the liberation from a foreign yoke and strengthening of the royal power. В армянском эпосе “Сасна Црер” и в средневековой историографии разными мотивами реализуется гипермотив охоты. В частности, в вариантах эпоса и в книгах средневековых авторов – Мовсеса Каганкатваци, Степаноса Орбеляна, Фавстоса Бузанда и Мовсеса Хоренаци, встречаются мотивы нахождения местa охоты, освобождения или нахождения охотничьей горы или леса, нахождения в том же месте спрятанной от героев церкви, убийства во время охоты и т. д. Сопоставление схожих мотивов в устной и книжной традиции не только дает возможность отследить связь и взаимовлияния традиций, но также показывает важное функциональное и сюжетообразующее значение мотивов охоты. В тематико-идейном плане созданиe или нахождениe место охоты символизирует освобождение от чужеземного ига и укрепление царской власти.
Keywords: Բանասիրություն; Գրականություն